Desperado - Rodriguez, Robert, (Robert Anthony), 1968-; Borden, Bill.; Banderas, Antonio; Almeida, Joaquim de, 1957-; Hayek, Salma, 1968-; Buscemi, Steve, 1958-; Marin, Cheech; Tarantino, Quentin; Navarro, Guillermo; Columbia Pictures; Los Hooligans Productions; Columbia Pictures Industries; et al. (Culver City, Calif. : Columbia Pictures Industries : Columbia Tristar Home Entertainment, 2003)
A mysterious guitar player seeks vengeance against the men who murdered his girlfriend.
Originally released as a motion picture in 1995.
Sequel to the film El Mariachi.
Director of photography, Guillermo Navarro ; editor, Robert Rodriguez ; music, Los Lobos.
Antonio Banderas, Joaquim de Almeida, Salma Hayek, Steve Buscemi, Cheech Marin, Quentin Tarantino.
MPAA rating: R.
DVD, Region 1, Widescreen presentation (aspect ratio 1:85: 1); Dolby stereo, DTS and Dolby Digital 5.1.
Keywords: Revenge -- Drama; Venganza -- Teatro; Feature films; Action and adventure films; Films for the hearing impaired